The thermal properties of water-based hybrid nanofluid (CU-AL2O3) beyond an inclined plane - Mohd Rusdi, Nadia Diana; Mohamed Isa, Siti Suzilliana Putri; Md Arifin, Norihan; Bachok @ Lati, Norfifah (Vinča Institute of Nuclear Sciences, Belgrade, 2022)
The thermal properties of radiating water-based hybrid nanofluid with nanoparticles Cu-Al2O3 over an inclined shrinking plane are investigated. The govern¬ing equations in this model are transformed into similarity equations. Then, the boundary value problem solver (bvp4c) in MATLAB software is used numerically to solve these similarity equations. It has been discovered that utilizing MATLAB software the dual numerical solution occurs for certain values of the nanoparticle volume fraction and the suction parameter. Therefore, the skin friction coefficient and Nusselt number increase due to the effect of radiation and suction parameter. As a result of the findings, we were able to identify that the increasing nanoparticle volume fraction and the suction parameter cause the reliable numerical findings for velocity profile to enhance. When the first solution of suction parameter is increased, the skin friction coefficient and the local Nusselt number increase. Meanwhile, in the presence of the radiation parameter, the temperature of both solutions rises.